Treatment of journalistic genres in the information of Euro-Mediterranean press - Sabés Turmo, Fernando; Carniel Bugs, Ricardo (Historia y Comunicación Social, 2014)
The information generated in the Euro-Mediterranean area has currently great importance, not only due to the events known as the Arab Spring. Previously, many initiatives were already underway in different forums such as the Barcelona Process: Union for the Mediterranean, the European Neighbourhood Policy of the European Commission, and the recommendations of the Report of the High Level Group of the Alliance of Civilizations reflected in the 2007-2009 Action Plan. This article analyzes the journalistic genres used by 16 newspapers in the treatment of the information related to the Euro-Mediterranean area: El Khabar and El Watan (Algeria), Il Corriere della Sera and La Repubblica (Italy), ABC and El País (Spain), The Guardian and The Times (UK), Al Ahram and Al Dostur (Egypt), Al Massae and As Sabah (Morocco), Le Figaro and Le Monde (France) and Al Thawra and Al Watan (Syria). In total, we examined 1.254 units of analysis which are collected between 9 and 22 March 2009. The results show that news is the major journalistic genre, indicating a lack of innovation in most of the analyzed newspapers.
Keywords: Journalistic genres; Information; Mediterranean; Newspapers